Eksperimen Pembelajaran Dengan Pendekatan Open-Ended Dan Contextual Teaching And Learning (Ctl) Terhadap Prestasi Belajar Matematika Ditinjau Dari Motivasi Siswa Kelas VIII Smp Muhammadiyah 1 Gatak Semester Genap Tahun Ajaran 2015/2016 - Afni Fitriana, Nur (2016)
The research aims to examined (1) the significant influence in the Open-Ended and Contextual Teaching and Learning approach toward mathematics learning achievement, (2) the significant influence in the motivation of student toward mathematics learning achievement, (3) the interaction between the learning approach and motivation of student toward mathematics learning achievement. The research quantitative type is quasi-experimental design. The research population and sample are 8th grade students of SMP Muhammadiyah 1 Gatak. The research sample used a census sample. The data collecting instruments were a test, questioner and documentation method. The data was analyzed with unbalanced two-way analysis of variance. The research with α = 5% result show that (1) there are significant influence in the Open-Ended and Contextual Teaching and Learning approach toward mathematics learning achievement, (2) there are significant influence in the motivation of student toward mathematics learning achievement, (3) there are no interaction between the learning approach and motivation of student toward mathematics learning achievement.